Adaptation and validation of the Person‐centered Care Assessment Tool (P‐CAT) to the Portuguese population. (10th January 2023) - Barbosa, Maria Miguel; Teixeira, Laetitia; Edvardsson, David; Paul, Constança; Yanguas, Javier; Afonso, Rosa Marina
Abstract: Background: The relevance of person‐centred care as an optimising approach to the quality of care provided to older adults has sparked the development of important instruments that measure this approach at residential care facilities and requires validation for the Portuguese population. Objectives: This study aims to adapt and validate the Person‐centered Care Assessment Tool (P‐CAT) to the Portuguese population. Methods: The P‐CAT assesses the level of person‐centred care provided by residential care facilities, according to staff. The process of adapting the P‐CAT to the Portuguese population includes its translation, backtranslation and a pilot study. To recruit participants for the validation study, we contacted the Portuguese residential care facilities with emails provided in the official registries, and the study was also divulged on social media. Results: The study had the participation of 573 staff members. The mean score of P‐CAT was 50.76 (SD = 7.65). The exploratory factor analysis showed three dimensions: the extent of care personalisation, the amount of organisational support and the degree of environmental accessibility. The results show good internal consistency for the total scale (α = 0.809) and good temporal stability in the test–retest assessed by intraclass correlation coefficient (0.893). Conclusions: This version of the P‐CAT for the Portuguese population has shown adequate psychometric properties and contributes to the study of care provided at residential care facilities in Portugal through self‐reporting from staff. Implications for practice: The availability of this instrument is useful for professional practice and research purposes and supports technical and scientific advancements that are necessary for the evolution of care frameworks.